Fourier series method for function synthesis of space RCCC mechanism - C. Li; X. G. Li (Metalurgija, 2025)
Metallurgical equipment needs to use a large number of linkage mechanism to achieve the given movement requirements, compared with the plane four-bar mechanism, the movement of the spatial mechanism is more stable, this paper through the study of the spatial RCCC mechanism, to establish a new method to realize the function synthesis of the mechanism of the algebraic solution, for the spatial mechanism in the metallurgical equipment in a wide range of applications to lay a theoretical foundation.